Rock and palaeomagnetic properties of randomly oriented basaltic blocks from lonar crater ejecta, India - Arif, Md.; Basavaiah, N.; Misra, S. (My University, 2012)
The preliminary investigation of rock and palaeomagnetic properties of the basaltic blocks deposited within the continuous ejecta around the Lonar crater during impact shows that these ejecta basalts, in general, have low NRM/χ compared with the average unshocked basalt from the ESE of Lonar crater. These ejecta basalts also have low REM with few exceptions. The HC component of these ejecta basalts are random but showing a broad concentration around the average HC component of shocked basalts from around the crater rim suggesting influence of shock induced magnetic field beyond the modification stage of formation of the Lonar crater.
Keywords: Lonar crater ejecta; Palaeomagnetic properties; Rock